Earth pressure and earth-retaining structures - Clayton, C. R. I.; Milititsky, J.; Woods, Rick I.; Bond, Andrew J. (CRC Press, 2014)
"Retaining structures form an important component of many civil engineering and geotechnical engineering projects. Careful design and construction of these structures is essential for safety and longevity. This new edition provides significantly more support for non-specialists, background to uncertainty of parameters and partial factor issues that underpin recent codes (e.g. Eurocode 7), and comprehensive coverage of the principles of the geotechnical design of gravity walls, embedded walls and composite structures. It is written for practising geotechnical, civil and structural engineers; and forms a reference for engineering geologists, geotechnical researchers and undergraduate civil engineering students"--